Simultaneous Extraction of Polysaccharides and Isoflavone from Semen sojae Preparatum and Assay for Anti-a-Glucosidase Activity - Ge, Xizhen; Zhang, Jing; Lin, Qiang; Tian, Pingfang (Asian Journal of Chemistry, 2011)
Isoflavone from Semen sojae preparatum (ISSP) was extracted with 80 % ethanol by ultrasonic method. The extract was subjected to macroporous resin AB-8, eluted by 80 % ethanol and analyzed with HPLC. The main isoflavone included genistin (1076.80 μg/g), daidzein (910.22 μg/g) and genistein (1128.61 μg/g). Subsequently, polysaccharides from Semen sojae preparatum (PSSP) present in sediments were extracted with distilled water using ultrasonic method, the total crude polysaccharides accounted for 13.3 mg/g, which were further purified, two of them, PSSPI and PSSPII manifested molecular weight of 9500 and 7000 Da, respectively. By establishment of in vitro a-glucosidase inhibitor models, the inhibitory rate of ISSP to a-glucosidase was shown to be 40.6%, while both PSSPI and PSSPII exhibited anti-a-glucosidase activity of 3 %.